Performance testing of air flow sensor - Sng, Ivan Weilong (2017)
This report presents a measurement study to investigate the accuracy of the Average Pitot Tube (APT) designed by NTU research team and focus the functionality of the APT using close to the damper in order to predict the air flow after the damper, which is common in the industrial applications. The entire experiment was conducted based on the testing bed simulated in the laboratory. An airflow testing bed that consists of a vortex flow meter, differential pressure transmitter, a centrifugal fan, air ducts, electrical damper and NI board were selected to set up the simulation which all of the measurements was collected in the LabVIEW user interface. Fan voltage and damper angle are varied from the LabVIEW user interface. The collected data were send to MATLAB to plot the data with uncertainties taking into consideration. Results show that the K factor is linearly proportional to the flow rate of the air. The K factor is more related to the flow rate than the damper angle. Hence, K factor depend on the flow rate rather than the positon of the damper angle. In this paper, a new model is propose such that K factor is linear dependent to flow rate Q. The Q uncertainty is less than K uncertainty, as a result the prediction of the K factor is better using the Q. Future work would be required to further reaffirm the efficiency and effectiveness.